Women’s Political Participation and Community Development: A Case Study of Northern Division Kabale Municipality. - Ahimbisibwe, Maxensia (Kabale University, 2024)
The study investigated the relationship between women’s political participation and community development in Northern Division, Kabale Municipality. The study objectives were to evaluate the extent and nature of women's political involvement in the area, examine the impact of their participation on community development efforts, and identify barriers hindering their political engagement and the implications for community progress. A mixed-methods approach and a correlational research design were employed for the study. A sample of 443 participants was drawn from the target population using stratified random sampling and purposive sampling methods. Data collection involved surveys, structured interviews, and semi-structured interviews to capture insights into women's participation in local governance, electoral activities, and community decision-making platforms. The findings indicated that women are actively engaged in local politics and decision-making. However, disparities persist in their access to leadership roles, highlighting challenges in achieving gender equality in political representation. The analysis also revealed a significant positive correlation between women's political participation and improved community development outcomes. The study concluded that the findings underscore the importance of addressing barriers to women's political participation to enhance community development and promote gender equality. Efforts to empower women politically must prioritize dismantling systemic barriers and fostering an enabling environment for women's engagement in political processes.